Money Politics Islamic Economic Perspective In The 2020 Sambas Regency Regional Elections - Munadi; Yessi Mayasanti; Deni Irawan (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2023)
This study departs from the regional elections is a manifestation of the Democratic Party, where at that time the people are directly involved in democratic life in Indonesia. Before the regional head election took place Regional Head candidates along with their success team, they conducted a campaign from one place to another, the purpose and purpose of the campaign is none other than their vision and mission as a candidate for Regional Head and far more important than all that is for the public to vote for the regional head candidate. Usually, candidates for regional heads promise everything, whatever the form, both for the benefit of the local people and to advance the economy of the region. The purpose of this study was to conduct an assessment and analysis related to the criteria for actions that can be considered as money politics in the implementation of the Sambas regency election in 2020. To describe and analyze money politics in the 2020 Sambas regency Regional Head election from the perspective of Islamic Economics. The method used in this study is descriptive qualitative phenomenological approach. Data collection was conducted with research instruments in the form of a list of interviews, with data collection techniques in the form of interviews, observations and documentation. The source of data in this study is primary data sourced from interviews with people who directly intersect with money politics, responses of religious leaders and successful teams, namely field implementers from prospective Regents and vice regents in the Sambas regency election in 2020. The data analysis techniques in this study are data reduction, data presentation, conclusion or verification. Based on the results of the study, the criteria for actions that can be considered as money politics in the implementation of the Sambas regency election in 2020 include the provision of basic necessities, souvenirs in the form of sarongs, in the form of cash veils are given to fill the recitation cash, Based on the principles of Islamic Economics, the money politics that occur in Sambas regency are not in accordance with the principles of Islamic economics, because they are carried out unfairly, irresponsibly, and do not limit individual freedom.